Uang Panai: Between Tradition And Perception Among Bugis, Moronene, And Sundanese Culture In Indonesia - Sain, Yuliyanah; Sanhas, Tasman; Nufus, Siti Hayatun; R, Novita P; Amin, Syarif (Journal of English Language and Education, 2025)
The "Uang Panai" (bridewealth) custom holds significant cultural weight in various Indonesian ethnic groups, particularly among the Bugis, Moronene, and Sunda. This study investigates the intricate relationship between tradition and contemporary perceptions surrounding Uang Panai in these three distinct communities. Utilizing a qualitative approach with an ethnographic design, the research employed in-depth interviews and participant observation with community elders, young adults, and cultural figures in selected regions of South Sulawesi (Bugis), Southeast Sulawesi (Moronene), and West Java (Sunda). Key findings reveal diverse interpretations and practices of Uang Panai, ranging from its symbolic value as a reflection of family honor and social status among the Bugis, to its more pragmatic function as a shared financial responsibility in the Moronene community. In contrast, the Sundanese perspective, while acknowledging traditional dowry, shows less emphasis on a comparable "Uang Panai" concept, often prioritizing the couple's readiness. The study concludes that while Uang Panai remains a fundamental cultural element, its execution and societal acceptance are continually shaped by evolving socio-economic conditions and generational perceptions, leading to varying degrees of adaptation and preservation across these Indonesian ethnic groups.